Wilhelm Fliess papers - Fliess, Wilhelm, 1858-1928.; Fliess, Conrad
Correspondence, writings, a reminiscence, and clippings chiefly concerning a plagiarism controversy involving Fliess, Sigmund Freud, Hermann Swoboda, and Otto Weininger related to the publication in 1903 of Weininger's Geschlect und Charakter which contained theories on bisexuality similar to those developed and published by Fliess in the pamphlet, In Eigener Sache. Includes draft and published versions of Fliess's pamphlet. Also includes letters from Josef Breuer and Oscar Rie and reminiscences by Fliess's son, Conrad Fliess.
Physician.
Collection material in German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Breuer, Josef, -- 1842-1925 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Rie, Oscar, -- 1863-1931 -- Correspondence; Swoboda, Hermann, -- 1873-1962.; Weininger, Otto, -- 1880-1903.; Bisexuality; Plagiarism; Physicians